A review of Cunaxidae (Acariformes, Trombidiformes): Histories and diagnoses of subfamilies and genera, keys to world species, and some new locality records - Skvarla, Michael J. (Pensoft Publishers, 2014)
Abstract. Cunaxidae are predaceous mites found in a variety of habitats. This work provides comprehensive keys to world subfamilies, genera, and species. Diagnoses and historical reviews are provided for subfamilies and genera. Cunaxa boneti, C. denmarki, C. exoterica, C. floridanus, C. lehmanae, C. lukoschusi, C. metzi, C. myabunderensis, C newyorkensis, C. rackae, C. reevesi, and C. reticulatus are moved to Rubroscirus and C. otiosus,﻿ C. valentis, and C. rasile are returned to Rubroscirus. Cunaxoides neopectinatus is moved to Pulaeus. Neocunaxoides pradhani and N. gilbertoi are transferred to Scutopalus. Pulaeus minutus and P. subterraneus are moved to Lupaeus. Pseudobonzia bakari, P. malookensis, and P. shamshadi are transferred to Neobonzia. Dactyloscirus bifidus is transferred to Armascirus. Scirula papillata is reported from the Western Hemisphere for the first time. Armascirus ozarkensis, A. primigenius, and Dactyloscirus dolichosetosus are reported from new localities.